2018
DOI: 10.1158/1535-7163.mct-17-0738
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Doxorubicin-Loaded Bacterially Derived Nano-Cells for the Treatment of Neuroblastoma

Abstract: Advanced stage neuroblastoma is an aggressive disease with limited treatment options for patients with drug-resistant tumors. Targeted delivery of chemotherapy for pediatric cancers offers promise to improve treatment efficacy and reduce toxicity associated with systemic chemotherapy. The EnGeneIC Dream Vector (EDV) is a nanocell, which can package chemotherapeutic drugs and target tumors via attachment of bispecific proteins to the surface of the nanocell. Phase I trials in adults with refractory tumors have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The authors demonstrated that the EGFR-targeted nanocells enhanced penetrance of doxorubicin compared to non-targeted doxorubicin loaded nanocells and doxorubicin without a delivery vehicle, resulting in increased apoptosis. These findings were confirmed in an orthotopic xenograft model [156].…”
Section: D In Vitro Models: Spheroidsupporting
confidence: 59%
“…The authors demonstrated that the EGFR-targeted nanocells enhanced penetrance of doxorubicin compared to non-targeted doxorubicin loaded nanocells and doxorubicin without a delivery vehicle, resulting in increased apoptosis. These findings were confirmed in an orthotopic xenograft model [156].…”
Section: D In Vitro Models: Spheroidsupporting
confidence: 59%
“…Between them, the use of hyperosmotic solutions [56], FUS [155], biodegradable implants [156], and CED [157] are extensively used and/or investigated in the clinic for their safety and efficacy. On the other hand, to our knowledge, only one model of targeted nanoparticle is under investigation in humans for the treatment of GBM [158]. While these strategies were shown to be effective, currently they can increase overall patient survival only by a few weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Another phase 1 study is testing an EGFR-directed mitoxantrone-loaded EDV (EEDVSMit) in children with r/r solid tumors (NCT02687386). A third clinical trial utilized EGFR(V)-EDV-Dox in patients with recurrent glioblastoma (NCT02766699), after it had shown significant prolongation of overall survival in two orthotopic human neuroblastoma xenograft models [ 192 ]. Eight of 14 patients completed one cycle, four more than one cycle of therapy; median PFS was 1.6 months, 2/14 patients had a PFS >6 months, and median OS was 9.7 months.…”
Section: Payload Delivery Using Multispecific Constructsmentioning
confidence: 99%